MODEL OF ENFORCEMENT OF REGIONAL REGULATIONS (PERDA) AGAINST STREET VENDORS (PKL) BY THE POLICE CIVIL SERVANTS UNIT (SATPOL PP) BASED ON PARTICIPATORY EMPOWERMENT IN BATANG REGENCY - Trianingrum, Nuni; Hafidz, Jawade (UNISSULA Semarang, 2023)
The law enforcement model against street vendors conducted by Satpol PP is likely to promote violence. This way of causing the impact of social conflict, ie fued or physical clash with violence between members of Satpol PP and sreet vendors. If this incident there is no handling will then cause stability of security and development will be disrupted. To that end, the author offers a more humane way through a participatory empowerment approach. It is hoped that participatory approach models can reduce social conflict.Keywords : SATPOL PP, Social Conflict, Model of Participatory Empowerment.